Impedance of Inner Saturated Soil to Horizontally Vibrating Large-Diameter Pipe Piles - Jiang Xie (Shock and Vibration)
An analytical solution for the inner soil impedance of saturated soil to a horizontally vibrating large-radius pipe pile was presented. Based on the porous media theory and the assumption that the vertical normal stress is zero, the closed solution of the inner soil impedance of the saturated soil to the movement of the large-diameter pipe pile is obtained. This analytical solution considers the influence of saturated soil parameters on the impedance of the core soil of large-diameter pipe piles. Through numerical examples, the variation law of the inner soil impedance with pile radius, pile length, dimensionless frequency, compression coefficient, effective permeability coefficient, and porosity was analyzed and the pile radius corresponding to effective inner soil impedance is determined.